Interrater and Intrarater Reliability of Musculoskeletal Ultrasonographic Findings for the Common Extensor Tendon of the Elbow. (July 2021) - Patel, Vikas; Esfahani, Ali; Ahmadi, Roozbeh; Forney, Michael; Apiafi, Mary; King, Dominic; Genin, Jason
Objectives: This retrospective case study evaluated the interrater and intrarater reliability of seven common extensor tendon pathologic features on musculoskeletal ultrasonography (MSK-US). Materials and Methods: A cohort of 50 patients were imaged due to presenting with atraumatic nonradicular lateral elbow pain. Three experienced and two novice readers rated the images on two separate occasions, and AC1 and kappa coefficients were calculated for each feature. Results: The interrater reliability was fair with respect to fascial thickening/scarring (AC1 = 0.26), tearing (AC1 = 0.35), tendon thickening (AC1 = 0.38), and intratendinous calcification (AC1 = 0.33); substantial for enthesophytes (AC1 = 0.80); and near complete for hyperemia (AC1 = 0.83) and hypoechogenicity (AC1 = 0.92). Intrarater reliability was moderate for fascial thickening/scarring (κ = 0.48), tearing (κ = 0.41), tendon thickening (0.47), intratendinous calcification (κ = 0.56), and hypoechogenicity (κ = 0.47); substantial for hyperemia (κ = 0.71); and almost perfect for enthesophytes (κ = 0.86). Conclusion: MSK-US may be a reliable tool to determine soft tissue changes in common extensor tendon pathology.